1987
DOI: 10.1111/j.1432-1033.1987.tb11216.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, accumulation and turnover of carbamoylphosphate synthetase and phosphoenolpyruvate carboxykinase in cultures of embryonic rat hepatocytes

Abstract: Glucocorticosteroid, thyroid hormones and cyclic AMP can induce the synthesis of carbamoylphosphate synthetase and phosphoenolpyruvate carboxykinase in cultures of hepatocytes as soon as these cells differentiate from the embryonic foregut. The low levels of both enzymes that can accumulate in such still protodifferentiated hepatocytes are due to low levels of enzyme synthesis. In cultures, the rate of synthesis of both enzymes increases continually in the presence of hormones, showing that maturation of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The most striking result, however, is the fact that from that moment onwards, the number of cells accumulating enzyme increased simultaneously in all four cell cohorts, i.e., enzyme accumulated in hepatocytes independent of the position of the cell in the cell cycle. From the fact that we have no indication for a difference in biological half life of carbamoylphosphate synthetase protein in embryonic hepatocytes when compared to adult hepatocytes [29], we conclude that enzyme accumulation reflects enzyme synthesis. Figure 3D, in which ['HI-TdR was used as the first and bromodeoxyuridine as the second label, shows that the carbamoylphosphate synthetase accumulation is retarded in the purely bromodeoxyuridine-labeled cell cohort only, i.e., in cells exposed to bromodeoxyuridine at the beginning of the S phase.…”
Section: Nonadhering Cells Experiments a Was Initiated ( I 0 H); 18mentioning
confidence: 52%
“…The most striking result, however, is the fact that from that moment onwards, the number of cells accumulating enzyme increased simultaneously in all four cell cohorts, i.e., enzyme accumulated in hepatocytes independent of the position of the cell in the cell cycle. From the fact that we have no indication for a difference in biological half life of carbamoylphosphate synthetase protein in embryonic hepatocytes when compared to adult hepatocytes [29], we conclude that enzyme accumulation reflects enzyme synthesis. Figure 3D, in which ['HI-TdR was used as the first and bromodeoxyuridine as the second label, shows that the carbamoylphosphate synthetase accumulation is retarded in the purely bromodeoxyuridine-labeled cell cohort only, i.e., in cells exposed to bromodeoxyuridine at the beginning of the S phase.…”
Section: Nonadhering Cells Experiments a Was Initiated ( I 0 H); 18mentioning
confidence: 52%
“…We have presently extended these results, showing that when steady-state conditions are reached after induction, i.e. when the enzyme content per average hepatocyte does not change anymore [22,23], the degree of intercelluar heterogeneity is higher for short-lived proteins (such as PEPCK [36]) than for long-lived proteins (such as CPS [36]) and higher when suboptimal (tenfold lower) concentrations of inducing hormones are present than when optimal concentrations are provided. Likewise, the degree of interhepatocyte heterogeneity that persists under steady-state induced conditions [37] is higher for mRNAs than for their respective proteins and higher for PEPCK mRNA than for CPS mRNA.…”
Section: Discussionmentioning
confidence: 66%
“…period [22,37,381, thus indicating regulation at both the transcriptional and translational level. Although naive embryonic rat hepatocytes can be induced to accumulate liver-specific proteins, their synthetic capacity is low [36]. We have observed that maturation towards the adult synthetic capacity in these hepatocytes in our in vitro culture system closely mimics hepatocyte maturation in vivo [23, 251. Immunostaining of cultured hepatocytes with antibodies directed against CPS and PEPCK has shown that the initiation of expression of both genes is a stochastic event [38].…”
Section: Introductionmentioning
confidence: 99%